Playful Activities to Develop Mathematical Thinking in High School Children - Bolaños Rodriguez, Nancy Guadalupe (2024)
The research focused on analyzing how a program of playful activities influences the development of mathematical thinking in early childhood children who attend the preparatory education level, a process of transition between mathematical notions and the basic contents of this area of knowledge. The study used a quantitative methodology and quasi-experimental design based on the comparison of an experimental and a control group. The study population included 70 students aged 5 to 6 years. Initially, a diagnosis was applied based on the mathematical thinking questionnaire that obtained a reliability level of A=.855, through which shortcomings were evidenced in both groups. The final results showed a significant improvement in the experimental group, while the control group showed no significant changes.